Lack of uniformity in the Israeli property tax system 1997-2017 - Avi Perez (Journal of Risk and Financial Management, 2020)
There are two different forms of property tax systems: value-based tax, which is used in most countries of the world, and area-based tax, which is used mainly in Central and Eastern Europe and developing countries in Africa. Area-based property tax provides more stable and predictable budget revenues. It is simpler to administer and scores worse on equity grounds from the perspective of the ability-to-pay principle of taxation. Against this background, Israel's property tax system, known as Arnona, is complex, spatially diversified, and causes a lack of uniformity that leads to tax distortion. This paper's primary purpose is to identify the weaknesses of Israeli property tax from 1997 to 2017 and indicate how to improve the property tax system. This paper is based on case studies from four of the most important cities in Israel: Tel Aviv, Jerusalem, Haifa, and Beersheba, which have four different measurement methods for calculating property tax. Unique data were collected from the Israel Central Bureau of Statistics. According to this analysis, it was found that there are substantial differences in property tax between the four cities over the two decades analyzed. The main weakness is the lack of uniformity of the taxation system; the solution is to unify the measurement of real estate area for tax purposes using drone technology.
Keywords: 330; property tax; Israel; information and communication technology